Surprised by joy [compact disc,unabridged] : the shape of my early life - Lewis, C. S. (Clive Staples), 1898-1963 (Blackstone Audiobooks, 2000)
C.S. Lewis here shares the story of his personal spiritual journey. He describes how his "search for joy" led him from the conventional Christianity of his childhood to a youthful atheism, and finally back to an assured Christianity compatible with his formidable intellect. Lewis's "surprise" holds continuing interest not only for admirers of his work but for any modern seeker concerned with the compatibility of the rational and the spiritual.